Uttar Pradesh Five Year Plan A Progress Review - Planning Commission (Planning Commission, 1953)
Planning in a democracy evolves around and is always subservient to liberty. Economic goals have to be achieved without the loss of fundamental liberties, and by the use of incentives rather than compulsion. Although “free enterprise” and "laissez-faire” may be replaced by a planned economy, political democracy should grow and flourish. This we have ensured by adult Suffrage, the lengthening and widening of our educational ladder and freedom of thought and speech. Our Constitution itself is the surest safeguard against our ‘planning’ being anything more than the fulfillment of the wishes of our people, “the servant of our freedom that will bring, another part of our common life within the control of o: r social wisdom.” The National Planning Commission has indicated the key-note of Planning in India to be a process of development which will raise living standards and open out to the people new opportunities for a richer, and more varied life”. The emphasis on development is based on the needs of an-under-developed economy which must aim at maximum productivity from existing-resources and potential of both materials and man-power. The State Plan, like the parent National Plan, has the same central objective.
A Progress Review
Government of Uttar Pradesh